A vitória de Albuino : campanhas modernizadas no Brasil e no Espírito Santo - Cassundé, Ronaldo Luiz (2008)
The research establishes a historical landmark for the appearance of the called modernized campaigns in Espírito Santo, by means of the analysis of the electoral victorious strategy of the candidate for the government Albuíno Azeredo in the state elections of 1990. One year before, the same phenomenon was shown in a national extent through the campaign carried out by Fernando Collor de Mello, elected president of the Republic. The study of the confluence between the new technologies of the information and the practices of the political propaganda from the military dictatorship introduced in 1964 allows a spacious vision on the qualitative transformations that, after the political opening in 1980, led to the incorporation of technical resources and procedures to the strategies of the candidates, favoring, in an advanced way, the appearance of the modernized campaigns.